Comparison of the lipid properties of healthy and pansteatitis‐affected African sharptooth catfish, Clarias gariepinus (Burchell), and the role of diet in pansteatitis outbreaks in the Olifants River in the Kruger National Park, South Africa. Issue 11 (2nd May 2013) - Huchzermeyer, K D A; Osthoff, G; Hugo, A; Govender, D
Abstract Pansteatitis has been identified in wild populations of sharptooth catfish, Clarias gariepinus (Burchell), and Nile crocodiles, Crocodylus niloticus Laurenti, inhabiting the same waters in the Olifants River Gorge in the Kruger National Park, South Africa. Mesenteric and pectoral fat tissue was investigated microscopically and by fatty acid analysis in healthy and pansteatitis‐affected catfish from both captive and wild populations. Variation in fatty acid composition between pectoral and mesenteric fat was noted. Composition of mesenteric fat differed between fish from various localities as a result of differences in diet. Pansteatitis in the captive population, resulting from ingestion of high amounts of dietary oxidized fat, reflected higher levels of unsaturated fatty acids within the mesenteric fat. Mesenteric fat of pansteatitis‐affected wild catfish was characterized by an increase in moisture content, a decrease in fat content and a decrease in stearic and linoleic acids. The n‐3 to n‐6 fatty acid ratio of mesenteric fat was higher in pansteatitis‐affected wild catfish than in healthy catfish from the same locality, reflecting higher polyunsaturated fat intake by pansteatitis‐affected fish. The possible role of alien, invasive, phytoplankton‐feeding silver carp, Hypophthalmichthys molitrix (Valenciennes), in the aetiology of pansteatitis in both catfish and crocodiles in the Olifants Gorge is discussed.